The prognostic value of global longitudinal strain in patients with myocardial infarction and preserved ejection fraction : a prespecified substudy of the REDUCE-AMI trial - Mars, Katarina; Hofmann, Robin; Jonsson, Martin; Manouras, Aristomenis; Engvall, Jan; Yndigegn, Troels; Jernberg, Tomas; Shahgaldi, Kambiz; Sundqvist, Martin G. (European Heart Journal Cardiovascular Imaging, 2025)
Aims The REDUCE-AMI trial showed that beta-blockers in patients with preserved left ventricular ejection fraction (LVEF) after acute myocardial infarction (AMI) had no effect on mortality or cardiovascular outcomes. The aim of this substudy was to evaluate whether global longitudinal strain (GLS) is a better prognostic marker than LVEF, and if beta-blockers have a beneficial effect in patients with decreased GLS. Methods and results REDUCE-AMI was a registry-based randomized clinical trial. Conventional echocardiographic parameters and GLS were obtained and a likelihood ratio test between models adjusted for age, sex, hypertension, smoking, diabetes, previous AMI, and multi-vessel disease was used to compare LVEF and GLS as prognostic methods. A Cox regression model evaluated the impact of beta-blocker treatment on the composite endpoint of death from any cause or new AMI. A total of 1436 patients (28.6% of the total population) were included in this substudy. Due to poor image quality or incompatible equipment, 324 (22.6%) patients were excluded from the analysis of GLS. The median GLS was 17.3%. The likelihood ratio test resulted in no difference (P = 0.56) when comparing the combination of GLS to LVEF. The results were robust when adding beta-blocker randomization status as an independent variable. Conclusion In patients after AMI with preserved LVEF, GLS did not add prognostic value regarding death from any cause or new AMI. In addition, beta-blocker treatment did not alter the prognostic information obtained from GLS. Consequently, this study does not support an additive value of GLS compared with standard echocardiographic measurement in this patient population.
Keywords: acute myocardial infarction; beta-blockers; global longitudinal strain; left ventricular ejection fraction